The Effect of Tai Chi on Cardiorespiratory Fitness for Coronary Disease Rehabilitation: A Systematic Review and Meta-Analysis - Yang, Ying-li; Wang, Ya-hong; Wang, Shuo-ren; Shi, Pu-song; Wang, Can (Frontiers in Physiology, 2018)
Background: Tai Chi that originated from China as a martial art is an aerobic exercise with low-to-moderate intensity and may play a role in cardiac rehabilitation. Aim: To systematically review the effect of Tai Chi on cardiorespiratory fitness for coronary disease rehabilitation. Methods: We performed a search for Chinese and English studies in the following databases: PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature Database, China Knowledge Resource Integrated Database, Wanfang Data, and China Science and Technology Journal Database. The search strategy included terms relating to or describing Tai Chi and coronary disease, and there were no exclusion criteria for other types of diseases or disorders. Further, bibliographies of the related published systematic reviews were also reviewed. The searches, data extraction, and risk of bias (ROB) assessments were conducted by two independent investigators. Any difference was resolved by consensus. RevMan 5.3.0 was used to analyze the study results. We used quantitative synthesis if the included studies were sufficiently homogeneous. And we performed subgroup analyses for studies with different control groups. To minimize bias in our findings, we used GRADEpro to grade the available evidence. Results: Five studies were enrolled—two randomized controlled trials (RCTs) and three nonrandomized controlled trials (N-RCTs)—that included 291 patients. All patients had coronary disease. ROB assessments showed a relatively high selection and detection bias. Meta-analyses showed that compared to other types of low- or moderate-intensity exercise, Tai Chi could significantly improve VO2max [MD=4.71，95% CI (3.58, 5.84),P＜0.00001], while Tai Chi seemed to be less effective at improving VO2max after high-intensity exercise; this difference, however, was not statistically significant [MD= -1.10，95% CI (-2.46, 0.26), P=0.11]. The GRADEpro showed a low level of the available evidence. Conclusion: Compared to no exercise or other types of exercise with low-to-moderate intensity, Tai Chi seems a good choice for coronary disease rehabilitation in improving cardiorespiratory fitness. However, owing to the poor methodology quality, more clinical trials with large sample size, strict randomization, and clear description about detection and reporting processes are needed to further verify the evidence. Trial registration number: CRD42017063773.